Chronic myeloid leukemia: a model for oncology - Hehlmann, Rüdiger; Berger, Ute; Hochhaus, Andreas (Annals of hematology, 2005)
Leukemias have traditionally served as model systems for research on neoplasia because of the easy availability of cell material from blood and marrow for diagnosis, monitoring and studies on pathophysiology. Beyond these more technical aspects, chronic myeloid leukemia (CML) became the first neoplasia in which the elucidation of the genotype led to a rationally designed therapy of the phenotype. Targeting of the pathogenetically relevant BCR-ABL tyrosine kinase with the selective kinase inhibitor imatinib has induced remissions with almost complete disappearance of any signs and symptoms of CML. This therapeutic success has triggered an intensive search for target structures in other cancers and has led to the development of numerous inhibitors of potential targets, which are being studied in preclinical and clinical trials worldwide. This review deals with some of the recent developments that have evolved since our last review in this journal in 2000 (Hehlmann R, Hochhaus A, Berger U, Reiter A (2000) Current trends in the management of chronic myelogenous leukemia. Ann Hematol 79:345-354).